Study on the interface reaction layer of hydrogen reduction hot-rolled high-strength steel hot-dip galvanizing. (1st March 2022) - Liu, Yihao; Ding, Chengfa; Li, Jianchao; Lu, Rui; Wu, Guangxin; Zhang, Jieyu
Abstract: In this paper, the instability mechanism of the Fe-Al inhibition layer produced by the interfacial reaction in the Al-containing zinc melts on the hydrogen-reduced steel is studied in detail. The results show that the surface morphology of hydrogen-reduced hot-rolled steel at different temperatures is mainly divided into porous and dense states. Due to the different surface activity of the steel after hydrogen reduction, the reaction degree of the galvanized interface is also significantly different. When the Al content is 0.2 wt%, no Fe-Al inhibition layer is detected at the interface. After that, the influence of Al content on the interface inhibition layer was explored. The research results showed that under the same reduction temperature and inhibition time, the higher the Al content, the more obvious the inhibition layer formed at the interface. Finally, by extending the dipping time, it was confirmed that the Fe-Al inhibition layer had undergone a destabilization and cracking transformation process, that is, the zinc solution permeated the Fe-Al inhibition layer, and the iron interface and the liquid zinc were in direct contact, resulting in the formation of the Fe-Zn outburst structure, which was also aggravated the process of breaking the Fe-Al inhibition layer.